2008
DOI: 10.1007/s10157-008-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Lupus nephritis associated with positive MPO-ANCA in a patient with underlying autoimmune hemolytic anemia

Abstract: A 19-year-old female was admitted with general malaise and systemic edema. She had been diagnosed as having autoimmune hemolytic anemia (AIHA) eight years earlier and was successfully managed with oral prednisolone. During the current admission, she was diagnosed as having systemic lupus erythematosus (SLE) based on the presence of renal involvement, hematological abnormalities, and antinuclear and anti-double-stranded DNA antibodies, along with a recurrence of AIHA; her serology revealed a high myeloperoxydas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several cases considered to have ANCA-associated GN concurrent with LN have been reported [2][3][4][5][6][7][8][9][10]. Recently, Yu et al [4] reported that approximately 20 % of 152 patients who were classified as LN IV-G had crescentic GN and that approximately 30 % of cases with crescentic LN were seropositive for ANCA in a retrospective study of 327 patients with LN.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several cases considered to have ANCA-associated GN concurrent with LN have been reported [2][3][4][5][6][7][8][9][10]. Recently, Yu et al [4] reported that approximately 20 % of 152 patients who were classified as LN IV-G had crescentic GN and that approximately 30 % of cases with crescentic LN were seropositive for ANCA in a retrospective study of 327 patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…So far, very few reports have referred to the synchronicity of crescents in patients with ANCA-associated GN overlapping with LN. Of the cases reported to date with detailed pathologic findings, most had only cellular [3,5,7,10] or fibrocellular [6] crescents, although one case with different stages of crescents has been reported [9]. The existence of a link between ANCA seropositivity and SLE in the development of GN has been discussed [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations